Tumor‐induced osteomalacia combined with acromegaly: A case report. Issue 1 (2nd September 2022) - Li, Xiang; Ni, Xiaolin; Chai, Xiaofeng; Wang, Linjie; Jiang, Yan; Jing, Hongli; Huo, Li; Wu, Huanwen; Yao, Yong; Jin, Jin; Feng, Bin; Xia, Yu; et al.
Abstract: Both acromegaly and tumor‐induced osteomalacia (TIO) are rare diseases caused by an excess hormone secreted by neuroendocrine neoplasms, which are growth hormone (GH) and fibroblast growth factor 23 (FGF23), respectively. GH elevates phosphate reabsorption via the effect of insulin‐like factor 1 (IGF‐1), while FGF23 inhibits phosphate reabsorption and reduces serum phosphate level markedly. A patient who developed a typical acromegaly appearance but was accompanied with height loss and hypophosphatemia for 2 years visited our hospital. Laboratory investigations showed GH and IGF‐1 hypersecretion, as well as hypophosphatemia caused by renal phosphate wasting. Magnetic resonance image revealed a pituitary somatotroph adenoma. Octreoscan scintigraphy also found a causative tumor on the right foot for hypophosphatemia. Then, he underwent resection of the tumor on the right foot. His serum phosphate returned to normal immediately but elevated gradually. Then, we removed the pituitary adenoma of the patient, and the GH and phosphate levels returned to the normal range. Here, we report the first case with acromegaly combined with TIO, the changing process of his phosphate concentration suggests an interesting concurrent effect of excess GH and FGF23 in this rare condition. Abstract : Both acromegaly and tumor‐induced osteomalacia (TIO) are rare diseases caused by excess hormone secreted by neuroendocrine neoplasms. We report on a patient who developed typical acromegaly appearance but accompanied with height loss and hypophosphatemia. Also present was growth hormone and IGF‐1 hypersecretion, a pituitary somatotroph adenoma, and a causative tumor on the right foot. This is the first case with acromegaly combined with TIO.